EFEKTIFITAS ANTIBAKTERI Vibrio sp. DARI EKSTRAK DAUN MANGROVE Rhizopora apiculata - Hitijahubessy, Hendro; Irmawati, Yuni (Pattimura University, 2023)
Research was carried out by analyzing the antibacterial ability of the ethanol extractof mangrove Rhizopora apiculata leaves against Vibrio sp. Maceration using 70%ethanol resulted in an extract yield of 3.09%. The highest average inhibition zoneresults were found in mangrove leaf extract at a concentration of 100% with aninhibition zone of 24.68 mm. The smallest inhibition zone was found in mangrove leafextract with a concentration of 6.25% with an inhibition zone of 3.85 mm, a positivecontrol inhibition zone (30 mg tetracycline) of 26.35 mm and a negative controlinhibition zone (DMSO 10%) of 0 mm. This can be seen from the results of theaverage inhibition zone which shows strong antibacterial activity of mangrove leafextract at a concentration of 100% and moderate antibacterial activity of mangroveleaf extract at a concentration of 75% to 50% and no antibacterial activity atconcentrations of mangrove leaf extract below 25 %, the positive control inhibitionzone (30 mg tetracycline) was 26.35 mm and the negative control inhibition zone(DMSO 10%) was 0 mm. Phytochemical analysis was also carried out on mangroveleaves with the results showing the presence of several visible secondary metabolites.The secondary metabolites found in Rhizopora apiculata mangrove leaves consist ofalkaloids, flavanoids, steroids, saponins and tannins.